A description of the tadpole of Megophrys "Brachytarsophrys" intermedia (Smith, 1921) - Tapley, Benjamin; Nguyen, Luan Thanh; van Le, Manh (Zootaxa, 2020)
Megophrys Kuhl and Van Hasselt are an Asian radiation of terrestrial frogs which are usually associated with montane forest (Mahony et al. 2017). The Annam horned frog (Megophrys intermedia) is reported from montane evergreen forest in Vietnam and Lao People’s Democratic Republic (Stuart 2005; Hendrix et al. 2008; Nguyen et al. 2009; Tran 2013; Orlov et al. 2015; IUCN 2017; Mahony et al. 2017). The IUCN Red List assessment for the species reports an elevational range of 782–1500 m asl (IUCN 2017) although the type locality was reported to be above 1500 m asl (Smith 1921), and Tran (2013) collected a specimen at 1515 m asl. Megophrys intermedia is assessed as Least Concern (IUCN 2017) and little is known about the reproductive behaviour and life history of the species. In Lam Dong Province (Vietnam), male M. intermedia call in March (Tran 2013); on the Langbian Plateau (Vietnam), male specimens are reported to call by day and by night from March to May and specimens called from within deep crevices between boulders in streams (Smith 1921); in Xe Kong Province (Laos), males call or guard egg clutches that are laid in water in July (Stuart 2005).